PATTERNS OF INTERACTION IN PEER FEEDBACK PROVISION TO THE STUDENTS’ EXPOSITORY WRITINGS - Mufiz, Ali; Fitriati, Sri Wuli; Sukrisno, Alim (Universitas Negeri Semarang, 2017)
This study investigated students’ nature in pair interaction due to its vital role in learning. Therefore this study was aimed to describe and to explain patterns of interaction in peer feedback, the aspects of writing the students were concerned within peer feedback, influences of pair interactions to the students’ writings, and the students’ perceptions and attitudes on peer feedback. This study mostly employed qualitative approach and a case study method. The result showed that five patterns emerged in pair interaction i.e. collaborative pairs, dominant/dominant pair, dominant/passive pairs, expert/novice pairs, and passive/passive pair. However, feedback provided by collaborative and expert learners contributed to the revision changes of their partner’s writings so that the development of writing aspects under these two patterns was better. Besides, other factors which contributed to the students’ writings were confounding variables such as student’s proficiency, writing capability, and teacher feedback. Thus these results endorsed the former studies e.g. Storch’s (2002b) study, Iris’ (2014) study, and Roberson’s (2014) study. Another result was that whole students had good perceptions and good attitudes on peer feedback provision. However, the bottom line of this study was that collaborative pairs and expert/novice pairs had better second writings.